INVESTIGATION OF SORPTION BEHAVIOR OF LEATHER PROCESSED WITH FILLERS OBTAINED FROM MODIFIED SILK HYDROLYSATE - Abbosbek Muxtarov; Akmal Yusupovich Toshev; Tulkin Jumayevich Kodirov (Modern American Journals, 2025)
This study investigates the sorption properties of leather treated with fillers obtained on the basis of modified silk hydrolysate. The research highlights the role of protein-based fillers in improving the structural and functional characteristics of chrome-tanned leather. Modified silk hydrolysate provides active functional groups that enhance the binding capacity of the filler with collagen fibers, thereby increasing water vapor permeability, moisture absorption, and hygienic performance.
Keywords: Leather, modified silk hydrolysate, fillers, sorption properties, collagen, eco-friendly technology